THE APPLICATION OF HUMAN RIGHTS IN HANDLING DEMONSTRATIONS IN THE CITY OF MAKASSAR FROM THE PERSPECTIVE OF SIYASAH SYAR'IYYAH - Farahdilla Mutiara Khansa; Eril (Jurnal Al Tasyri'iyyah, 2025)
This study aims to discuss the application of human rights in handling demonstrations in the city of Makassar from the perspective of Siyasah Syar'iyyah. This study is qualitative in nature. The research design is field research. The results of this study show that; Regarding the handling of demonstrations in the city of Makassar, there is a commitment on the part of the police to continue to improve transparency and accountability in the performance of every task, including the handling of demonstrations. In addition, it was found that the police have taken and will continue to take steps related to transparency and accountability in handling demonstrations. They are open to correction and even reporting to Propam, open to supervision by external institutions such as Komnas HAM, the Ombudsman, and community organizations, and open to communication with demonstration coordinators and the mass media during demonstrations. There are also efforts to evaluate and document the handling of demonstrations. In addition, repressive measures are only regulated under certain conditions. They are only used when absolutely necessary to overcome a real threat to life, widespread property damage, or significant disturbances to public order. However, repressive measures are only taken after persuasive measures have been exhausted. The police officers who handled the demonstrations had undergone training on human rights principles. This shows that there are benefits. It is an indicator of alignment with Siyasah Syar'iyyah. However, the use of excessive force indicates a violation of human rights. Among other things, it is mentioned that the implementation of human rights principles in handling actions is often far from ideal. The police may make mistakes in handling demonstrations that have the potential to violate human rights. Violations of human rights indicate a contradiction to the benefits. This is an indicator of a lack of alignment with Siyasah Syar'iyyah.